Lady in the water - Shyamalan, M. Night; Giamatti, Paul.; Howard, Bryce Dallas, 1981-; Wright, Jeffrey; Balaban, Bob.; Choudhury, Sarita; Doyle, Christopher, 1952-; Howard, James Newton; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2006)
Apartment building superintendent Cleveland Heep rescues what he thinks is a young woman from the complex swimming pool he maintains. When he discovers that she is actually a character from a bedtime story who is trying to make the journey back to her home, he works with his tenants to protect he new friend from the creatures that are determined to keep her in our world.
Title from container.
Special features :Theatrical trailer; Teaser trailer; 'Lady in the water': a bedtime story; Reflections of 'Lady in the water'; Auditions; Gag reel; Deleted scenes.
Director of photography, Christopher Doyle ; editor, Barbara Tulliver ; music, James Newton Howard ; costume designer, Betsy Heimann ; production designer, Martin Childs.
Paul Giamatti, Bryce Dallas Howard, Jeffrey Wright, Bob Balaban, Sarita Choudhury, Cindy Cheung, M. Night Shyamalan, Freddy Rodrg̕uez, Bill Irwin, Mary Beth Hurt.
MPAA rating: PG-13; for some frightening sequences.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital 5.1 EX surround, DVD-9, dual-layer.
Keywords: Maintenance -- Drama; Characters and characteristics in literature -- Drama; Monsters in literature -- Drama; Feature films; Thrillers (Television programs); Thrillers (Motion pictures); Fantasy films; Video recordings for the hearing impaired; Thriller -- Feature; Fantasy -- Feature; Mystery -- Feature; Feature films; Suspense films; Fantasy films; Mystery films